COMPUTATIONAL ANALYSIS OF DISEASE ASSOCIATED nsSNPs in MMP2 - H. JEMMY CHRISTY (International Journal of Pharma and Bio Sciences, 2013)
MMPs have significant role in pathological processes and are associated with cancer invasion, and metastasis, cartilage destruction in arthritis. Non-synonymous single nucleotide polymorphisms (nsSNPs) occurring in protein coding regions of MMP potentially affect their function, and results in diseases. In this study we performed an insilco analysis of SNPs associated with MMP2 genes. Total of 683 SNPs are reported for MMP2 gene, coding region. In that only 39 are nsSNPs and 46 SNPs are in UTRs, 277 SNPs are in intronic region of mRNA. Our postulation is based on nsSNPs in the coding region as well as SNPs in the UTR region. Only 8SNPs out of 39nsSNP were identified as deleterious and had significant impact in structural stability which was analyzed using modeled and mutant proteins and native protein structures. Hence, these SNPs can be used for the larger population based studies based on MMP2 associated diseases.